The Impact of Online Gaming on Social Skills among Fourth-Grade Students in a Semi-Urban Indonesian School - Rustina, Rustina; Suparjan, Edy; Saputra, Ady (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study aims to examine the influence of online gaming intensity on the social skills of fourth-grade students at SD Inpres Tonggorisa, a public elementary school in a semi-urban area characterized by limited digital literacy. Employing a quantitative approach with a correlational design, data were collected from 30 students using a structured questionnaire that measured the frequency of online gaming and social skills indicators based on the Social Skills Rating System (SSRS). The results of linear regression analysis revealed a significant negative relationship between the two variables. Students with higher gaming intensity demonstrated lower levels of cooperation, self-control, and communication. These findings support Erikson’s theory of psychosocial development and highlight the urgent need for collaboration between schools and families to foster adaptive digital literacy. The study contributes to the limited body of research on digital behavior in non-urban settings and underscores the importance of implementing context-based character education strategies in the digital era.